The influence of foliar buckwheat fertilization with copper, manganese and iron on selected parameters of its nectar production and seed yield - Liszewski, Marek; Chorbiński, Paweł (Polish Journal of Agronomy, 2021)
The aim of the study was to determine whether it is possible to increase the amount of nectar from buckwheat by fo- liar feeding with micronutrients (copper, manganese and iron), which simultaneously ensuring proper nutrition and thus increas- ing the seed yield. The field experiment was established using the randomized block design with the ‘Kora’ cultivar of buckwheat. In the experiment, there were three treatments of foliar fertiliza- tion with Cu (ADOB 2.0 Cu IDHA), Mn (ADOB Mn 2.0) and Fe (ADOB 2.0 Fe IDHA) in the form of new generation chelates, 100% water-soluble. No significant effect of the fertilization was observed on the nectar mass, the concentration of sugars in nec- tar, the sugar mass per 10 flowers of buckwheat, and the sugar mass per hectare (ha). Similarly, no significant differences were noted following the fertilization treatments in the mean values of yield components, such as, the number of seeds per plant and the mass of 1000 seeds